Teachers’ Strategies in Managing Inclusive Classrooms: A Qualitative Study at SD Negeri 244 Palembang, Indonesia - Sari, Inda; Ahyani, Nur; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to examine teachers’ strategies, challenges, and solutions in managing inclusive classrooms at SD Negeri 244 Palembang, providing insights into effective practices for diverse learners. A qualitative approach was employed, utilizing classroom observations and in-depth interviews with teachers, staff, and parents. Data were analyzed through SWOT analysis and thematic coding to identify patterns and critical factors in inclusive education. Three primary strategies emerged: (1) use of visual media, (2) differentiated instruction, and (3) collaborative teaching. Key challenges included resource limitations and difficulties in student assessment, which teachers addressed through professional development and positive behavior reinforcement systems. This study offers a nuanced perspective by integrating SWOT analysis with qualitative data, revealing how grassroots-level strategies can overcome systemic barriers in Indonesian inclusive education. The findings underscore the need for targeted teacher training, resource allocation, and policy support to sustain inclusive practices. Schools can adopt the identified strategies to enhance classroom management and student engagement. The research enriches the discourse on inclusive education by documenting context-specific solutions from a underrepresented setting, serving as a reference for educators and policymakers in similar environments.